Genetic analysis of resistance to rice blast: a study on the inheritance of resistance to the blast disease pathogen in an F3 population of rice - Ashkani, Sadegh; Yusop, Mohd Rafii; Shabanimofrad, Mahmoodreza; Harun, Abdul Rahim; Sahebi, Mahbod; Abdul Latif, Mohammad (Blackwell Verlag GmbH, 2015)
Blast caused by the fungus Magnaporthae grisea (Herbert) Borr. (anamorphe Pyricularia oryza Cav.) is a serious disease of rice (Oryza sativa L.). One method to overcome this disease is to develop disease resistant cultivars. Due to the genetic plasticity in the pathogen genome, there is a continuous threat to the effectiveness of the developed cultivars. Additional studies of the genetics of resistance, virulence stability and functional genomics are required to accelerate research into understanding the molecular basis of blast disease resistance. In this study, individual plants of the F3 population derived from Pongsu Seribu 2 and Mahsuri were used for pathogenesis assays and inheritance studies of blast resistance. The study was performed with two of the most virulent Malaysian M. grisea pathotypes: P7.2 and P5.0. For blast screening, plants were scored based on the IRRI Standard Evaluation System (SES). F3 populations showed a segregation ratio of 3R:1S for pathotype P7.2, indicating that resistance to this pathotype is likely controlled by a single nuclear gene. Chi-square analysis showed that the F3 families segregated in a 15R:1S ratio for pathotype P5.0. Therefore, locus interactions or epitasis of blast resistance occur against pathotype P5.0 in the F3 population derived from Pongsu Seribu 2 and Mahsuri. This can be explained by the presence of two independent dominant genes that when present simultaneously, provide resistance to the M. gresia pathotype P5.0. These results indicated that blast resistance in rice is due to the combined effects of multiple loci with major and minor effects. The genetic data generated here will be useful in the breeding of local cultivars for resistance to field blast. The methodology reported here will facilitate the mapping of genes and quantitative trait loci (QTLs) underlying the blast resistance trait.